Diversity and Spatial Distribution of Chromophytic Phytoplankton in the Bay of Bengal Revealed by RuBisCO Genes (rbcL) - Pujari, Laxman; Wu, Chao; Kan, Jinjun; Li, Nan; Wang, Xingzhou; Zhang, Guicheng; Shang, Xiaomei; Wang, Min; Zhou, Chun; Sun, Jun (Frontiers in Microbiology, 2019)
Phytoplankton are the basis of primary production and play important roles in regulating energy export in marine ecosystems. Compared to other regions, chromophytic phytoplankton are considerably understudied in the Bay of Bengal (BOB). Here, we investigated community structure and spatial distribution of chromophytic phytoplankton in the BOB by using RuBisCO genes (Form ID rbcL). High throughput sequencing of rbcL genes revealed that diatoms, cyanobacteria (Cyanophyceae), Pelagophyceae, Haptophyceae, Chrysophyceae, Eustigamatophyceae, Xanthophyceae, Cryptophyceae, Dictyochophyceae, and Pinguiophyceae were the most abundant groups recovered in the BOB. Abundances and distribution of diatoms and Pelagophyceae were further verified using quantitative PCR analyses which showed the dominance of these groups near the Equator region (p < 0.01) where upwelling was likely the source of nutrients. Further, redundancy analysis demonstrated that temperature was an important environmental driver in structuring distributions of Cyanophyceae and dominant chromophytic phytoplankton. Morphological identification and quantification confirmed the dominance of diatoms, and also detected other cyanobacteria and dinoflagellates that were missing in our molecular characterizations. Pearson’s correlations of these morphologically identified phytoplankton with environmental gradients also indicated that nutrients and temperature were key variables shaping community structure. Combination of molecular characterization and morphological identification provided a comprehensive overview of chromophytic phytoplankton. This is the first molecular study of chromophytic phytoplankton accomplished in the BOB, and our results highlight a combination of molecular analysis targeting rbcL genes and microscopic detection in examining phytoplankton composition and diversity.